Pengaruh Kode Etik Profesi Akuntan Dalam Kinerja Auditor Eksternal Kasus PT Wanaartha Life - Ma’ruf Dwi Putra; Ahmad Lintang Abdul Haq; Abrar Rizqi Destriawan; Muhammad Yusuf Arda Bily; Herlina Manurung (Journal of Creative Student Research, 2023)
Public Bookkeepers have a set of rules that directs the morals of the Public Bookkeeper calling which is distributed by IAMI, IAI, and by IAPI under the name Set of principles for the Public Bookkeeper Calling. The Public Bookkeeper proficient set of principles is utilized as a reason for public bookkeepers to have the option to act morally and become an assurance of value ethics in the public arena. Nonetheless, despite the fact that there is a general set of principles for the public bookkeeping calling that directs the activities of public bookkeepers, there are as yet numerous infringement committed by open bookkeepers, so this can cause outrages that discolor the great name of the public bookkeeping calling itself and diminish public confidence in open bookkeepers. This article means to make sense of narratively the utilization of standards and endeavors to uphold the implicit set of rules for the public bookkeeper calling so the review results are as per the proof found since there is no bookkeeping designing that is impeding to closely involved individuals. Not just that, it is suggested that all closely involved individuals mutually participate and cooperate to make upgrades to maintain the Set of rules for the Public Bookkeeper Calling.